Comparing the Usability, Ergonomics, and Extensibility of Desknet Trainer and Netcube Trainer as Computer Network Learning Props in Vocational Education - Arifuddin, Faizal; Hatta, Puspanda; Wihidayat, Endar Suprih (Universitas Sebelas Maret, 2022)
The first objective of this study was to compare the usability, ergonomics, and extensibility of computer network learning props in vocational education. The second objective of this research is to obtain recommendations for developing a computer network trainer according to the weaknesses found in the comparison of usability, ergonomics, and extensibility. This research is quantitative research with a counterbalanced design. The study was carried out in two counterbalanced replications. The research subjects were 11 Informatics and Computer Engineering Education students at Universitas Sebelas Maret. The objects of this research are the Desknet Trainer and the Netcube Trainer. The data collection technique used is a questionnaire. The data analysis technique used is descriptive statistics and the T-test. The results showed that the comparison of Desknet Trainer and Netcube Trainer showed that the quality of both was statistically equivalent. The comparison breakdown of usability, ergonomics, and extensibility shows that the Desknet Trainer has weaknesses in the usability and ergonomics domains. In contrast, the Netcube Trainer has weaknesses in the extensibility domains. The Desknet Trainer can be further developed to improve usability and ergonomics. Netcube Trainer can be further developed to increase extensibility.